EFL Students’ Perception of Using Smartphone for English Language Learning - Winda Septiana Sitanggang; Putri Herawati Manalu; Rista Yuli; Fedra Rolinca; M.Mahfud Irkhamni (International Journal of Pedagogy, 2024)
In this day and age, there is an increasing tendency towards utilizing smartphone for the purposes of language learning Overall, there is a significant acceptance of mobile learning among language learners, especially in terms of usefulness, efficiency, interactivity, and convenience. The main goal of this survey research was to investigate the perspectives of first-semester students at English Education Department towards mobile applications use for the purpose of learning English. Data on the study findings are reviewed in the discussion part in order to either corroborate or refute certain earlier research findings. The researchers collected data using a questionnaire adopted from Hidayati (2019). The finding shows that the students’ perception of using smartphone for language learning was in the level “Moderate” indicated by Mean=3.31 and SD= .655. This study might be helpful for future investigations on the use of cellphones to learn languages. It is anticipated that the study's conclusions will be beneficial to students as one of their resources when they wish to use cellphones for language learning